An extent analysis of 3PL provider selection criteria: A case on Turkey cement sector - Berna Bulgurcu; Gulsun Nakiboglu (Cogent Business & Management, 2018)
Outsourcing has become an increasingly popular means for businesses to improve their efficiency. Logistics outsourcing can be described as transferring some of the logistics functions to an external firm. This paper aims to identify the selection criteria that are used by logistics service providers in Turkey's cement sector in choosing the third-party service provider. By drawing focus on Chang's Extent Analysis on Fuzzy Analytical Hierarchy Process (FAHP), the present paper evaluates cost, service/operation quality, competencies, general attributes of firms and relational factors as the main criteria, and considers explanatory 29 sub-criteria. In doing so, a questionnaire that was prepared in the pairwise comparison model was used as a large sample to collect data from a total of 25 experts working in 14 cement companies. As a result, the analysis identifies service/operation quality as the most important one among the main criteria, and determines the service price as the most preferred criterion among the sub-criteria. The study and results both provides particular insight into a specific sector as it is based on the data collected from a large number of experts in one sector, and offers an opportunity for other sectors from the same point of view.
Keywords: 650